Manual on Training in Evaluation Techniques - Planning Commission (Planning Commission, 1995)
Programme evaluation has been a very Important part of the process of economic planning in India since the Fifties. The efficacy of the process and technique of evaluation depend largely on the personnel involved in collection of data, collating the materials and interpreting them. proper training of the persons involved has, therefore, always been considered an Important aspect of the Evaluation Organization. In order to have an effective and structured training programme a manual was prepared in 1979. However, much changes have taken place in economic policies, concepts and models in the period since then. A revised manual has therefore become necessary.
Programme Evaluation Organisation Planning Commission Govt. of India